Prospects of Interdisciplinary Research into the Problem of Resource Mobilization of Academic Staff - Garold E. Zborovsky; Polina A. Ambarova (National Research Mordova State University, 2024)
Introduction. Mobilization of the resource potential of academic staff is a key task of university management. The development of management approaches to its solution should be preceded by a comprehensive study of both the academic staff resources and management practices. The possibilities of research are provided by an interdisciplinary theoretical and methodological framework. The purpose of the article is to substantiate the possibilities of developing interdisciplinary foundations for the study of the mobilization of the academic staff resource potential and the prospects for empirical study. Materials and Methods. The theoretico-methodological nature of the article required the use of methods for generalizing and systematizing the provisions of interdisciplinary and disciplinary approaches and theories that have been developed by social and humanitarian science. The main directions for the exploration of the problem of academic staff resource potential in modern socio-humanitarian knowledge have been identified through the method of systematic analysis of literature. Results. The main result of the research is the substantiation of the theoretical and methodological framework for an interdisciplinary study of the mobilization of the academic staff resources. This justification is based on the "revision" of theoretical and methodological provisions of theories of education. The basic interdisciplinary theories are the theories of adult continuing education, professional development and education, non-cognitive human capital, social networks, scientific and educational knowledge. Community-based, resource-based, institutional, normative, and communicative approaches are in demand. The provisions of these theories and approaches are adapted to the subject of the study. An important result of the research is the substantiation of the interdisciplinary synthesis in the practices of university management. Discussion and Conclusion. The prospects for using the interdisciplinary framework in an empirical study dealing with evaluation and activation of academic staff resources are shown. The practical significance of the results lies in the development of a model of mobilization management of the academic staff resources.